Study on earthquake and tsunami hazard: evaluating probabilistic seismic hazard function (PSHF) and potential tsunami height simulation in the coastal cities of Sumatra Island - Triyoso, Wahyu; Kongko, Widjo; Prasetya, Gegar S.; Suwondo, Aris (Frontiers in Built Environment, 2024)
This study uses integrated geological, geodesy, and seismology data to assess the potential tsunami and Seismic Hazard Function (PSHF) near Sumatra's coastal cities. It focuses on estimating the possible level of ground shaking due to the seismic activity within the Sumatra Fault Zone (SFZ) and subduction zone. It uses the Peak Ground Acceleration (PGA) as a measure. The research shows varying frequencies and magnitude of seismic hazards between northern and central-south regions of Sumatra based on the fault segment length. An amplification factor that is based on the previous study is used. It is calculated through the horizontal-vertical Spectral Ratio (HVSR), which measures possible surface ground shaking. The Seismic Hazard Function (SHF) is calculated considering magnitudes 6.5 to 9.0 for subduction sources and 6.5 to 7.8 for SFZ sources. Also, the PGA based on the Maximum Possible Magnitude (MPE) is estimated, and tsunami heights are simulated to assess the possible hazard risk. The tsunami source model in this study is characterized by considering the possibility of the long-term perspectives on giant earthquakes and tsunamis that might occur in subduction zones around the off-coast of southern Sumatra Island. The potentiality source zone is characterized based on the utilization of the cross-correlation of correlation dimension (DC) based on the shallow earthquake catalog of 2010 to 2022 and the SHmax-rate of surface strain rate. Based on the MPE, the relatively high estimated PGA at the base rock was found around Mentawai and Pagai Utara islands at about 0.224g and 0.328g, with the largest estimated PGA based on the MPE at the surface with values of about 0.5g and 0.6g. The possible maximum tsunami height (Hmax) estimated based on source scenarios position around the west coast of Sumatera Island, such as for Kota Padang and Kota Bungus, reaches up to 12.0m and 22.0m, respectively. The findings provide valuable insight into seismic and tsunami hazards, benefiting future mitigation strategies.